Alterations in motor functional connectivity in Neonatal Hypoxic Ischemic Encephalopathy. (28th January 2022) - Jiang, Li; El-Metwally, Dina; Sours Rhodes, Chandler; Zhuo, Jiachen; Almardawi, Ranyah; Medina, Alexandre E; Wang, Li; Gullapalli, Rao P.; Raghavan, Prashant
ABSTRACT: Background: Neonatal hypoxic-ischemic encephalopathy (HIE) is the result of global hypoxic-ischemic brain injury in neonates due to asphyxia during birth and is one of the most common causes of severe, long-term neurologic deficits in children. Methods: Resting state fMRI (rs-fMRI) was used to assess potential functional disruptions in the primary and association motor areas in HIE neonates (n = 16) compared to healthy controls (n = 11). Results: Results demonstrate reduced intra-hemispheric resting state functional connectivity (rs-FC) between primary motor regions (upper extremity and facial motor regions) as well as reduced inter-hemispheric rs-FC in the HIE group. In addition, HIE neonates demonstrated increased rs-FC between motor regions and frontal, temporal and parietal cortices but decreased rs-FC with the cerebellum. Discussion: These preliminary results provide initial evidence for the disruption of functional communication with the motor network in neonates with HIE. Further studies are necessary to both validate these findings in a larger dataset as well as to determine if rs-fMRI measurements collected at birth may have the potential to serve as a prognostic marker in addition to the traditional combination of clinical measurements and conventional MRI.